Research progress of 3D printed poly (ether ether ketone) in the reconstruction of craniomaxillofacial bone defects - Su, Qiao; Qiao, Yixin; Xiao, Yile; Yang, Shuhao; Wu, Haoming; Li, Jianan; He, Xinlong; Hu, Xulin; Yang, Hui; Yong, Xin (Frontiers in Bioengineering and Biotechnology, 2023)
The clinical challenge of bone defects in the craniomaxillofacial region, which can lead to significant physiological dysfunction and psychological distress, persists due to the complex and unique anatomy of craniomaxillofacial bones. These critical-sized defects require the use of bone grafts or substitutes for effective reconstruction. However, current biomaterials and methods have specific limitations in meeting the clinical demands for structural reinforcement, mechanical support, exceptional biological performance, and aesthetically pleasing reconstruction of the facial structure. These drawbacks have led to a growing need for novel materials and technologies. The growing development of 3D printing can offer significant advantages to address these issues, as demonstrated by the fabrication of patient-specific bioactive constructs with controlled structural design for complex bone defects in medical applications using this technology. Poly (ether ether ketone) (PEEK), among a number of materials used, is gaining recognition as a feasible substitute for a customized structure that closely resembles natural bone. It has proven to be an excellent, conformable, and 3D-printable material with the potential to replace traditional autografts and titanium implants. However, its biological inertness poses certain limitations. Therefore, this review summarizes the distinctive features of craniomaxillofacial bones and current methods for bone reconstruction, and then focuses on the increasingly applied 3D printed PEEK constructs in this field and an update on the advanced modifications for improved mechanical properties, biological performance, and antibacterial capacity. Exploring the potential of 3D printed PEEK is expected to lead to more cost-effective, biocompatible, and personalized treatment of craniomaxillofacial bone defects in clinical applications.